Diabetes and the retinal changes in the eye: a threat to the sight - Srivastava, Namrata; Chandra, Mahesh; Nitesh (International Journal Of Community Medicine And Public Health, 2024)
This article discusses the importance of diabetic retinopathy, an eye disease associated with diabetes, which is a systemic disease. The research question addresses the impact of diabetes on the retina of the eye through infection and clinical features. This approach is designed to improve the relationship between early diagnosis and treatment of disease, including laser surgery, corticosteroid injections, and vitrectomy. This article focuses on chronic diabetic retinopathy and eye examination recommendations in the United States and the United Kingdom. To prevent and manage diabetic retinopathy, it is recommended that diabetic patients have regular eye examinations. The results of this study include the importance of good glycaemic control, injections, photocoagulation, and vitrectomy as treatment options. Intravitreal long-acting steroids may also temporarily improve visual acuity by reducing macular oedema. However, long-term use of the drug may cause side effects and may lead to cataracts, steroid glaucoma, and endophthalmitis. It may cause reasons. A recent study of the disease in India shows that the incidence of high blood sugar and its effects on the eye is mainly diabetic retinopathy, including cataracts, neovascular glaucoma and even retinal detachment, which are very dangerous for eye health. Therefore, it is important to inform patients about this disease and perform timely screening because patients need to be informed carefully.